Adopting a management innovation in a professional organization: The case of improvement knowledge in healthcare. Issue 5 (7th September 2015) - Hellström, Andreas; Lifvergren, Svante; Gustavsson, Susanne; Gremyr, Ida
Abstract : Purpose: – The purpose of this paper is to study critical practices when adopting improvement knowledge as a management innovation in a professional organization. Design/methodology/approach: – This paper is based on an action research approach, in which practitioners and researchers are seen as a part of a participative community generating actionable knowledge. Research involved gathering data over a five-year period through more than 250 interviews and 25 focus groups. Findings: – This paper identifies five critical practices for adopting a management innovation in a professional context: first, focussing on labeling and theorizing to create an organization's own vocabulary; second, focussing on the role of internal change agents; third, allowing for an evolutionary adoption process; fourth, building new professional competence through the change agents; and fifth, adopting a research-driven approach to the adoption of a management innovation. Practical implications: – For healthcare practitioners, this paper points to practices to consider when adopting improvement knowledge – for example, identifying the patient as the guiding principle and encouraging involvement and local change initiatives. For practitioners in other professionally driven organizations, this paper identifies critical practices for adopting a management innovation – for example, focussing on theorizing and labeling in order to create an organization's own vocabulary related to the professional context. Originality/value: – On a generic level, this paper contributes to the understanding of critical aspects when adopting management innovations in a professional organization. In a healthcare context, this paper points to the value of improvement knowledge for improving quality of care. Improvement knowledge is relatively new in healthcare, and this study provides an example of a hospital in which this management innovation helped transform the organization.